Reconceptualizing the Methodology of Tafsir Manuscript Studies: A Holistic Framework for Manuscript Analysis - M. Ziyadulhaq (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
The Qur’an has generated a rich scholarly legacy in the form of diverse exegetical works produced through the intellectual engagement of Muslim scholars. Understanding these works of tafsīr requires specific and systematic methods to achieve a comprehensive interpretation. To date, the discipline of tafsīr manuscript studies continues to face challenges arising from the lack of synchronization and systematic organization in previous scholarly discussions. This study sought to reexamine existing procedures for manuscript studies while proposing a new and more logical systematic framework. This study employed both methodological and historical approaches. Data were collected through the documentation of tafsīr manuscripts and classified into primary and secondary sources. The data were analyzed in depth using content analysis techniques based on a conceptual framework for manuscript codification. The findings formulate nine standardized and sequential components for the systematic study of tafsīr manuscripts: physiological aspects (nuskhat al-kitāb), the exegete’s biography (tarjamat al-mufassir), sources (maṣdar), method (manhaj), presentation technique (ṭarīqah), orientation (lawn), theological affiliation (ittijāh), as well as an evaluation of the manuscript’s weaknesses (salbiyyāt) and strengths (ījābiyyāt).